Pengaruh Konseling Kelompok Dengan Teknik Reinforcement Untuk Mereduksi Perilaku Prokrastinasi Pada Mahasiswa - Mia Mardayanti; Suryati Suryati; Lena Marianti (Journal of Society Counseling, 2023)
The purpose of this study was to find out how procrastination behavior is in students of the da'wah and communication faculties and how the effect of group counseling with reinforcement techniques is to reduce procrastination behavior in students of the da'wah and communication faculties. The research methodology used in this study is quantitative and the type of experimental research is in the form of a quasi-experimental (quasi experimental design). The population in this study amounted to 141 people and the sample of 14 people was taken 10%. In general, it was found that 2 people were in the high category with a percentage of 14%, 10 people were in the medium category with a percentage of 71%, and 2 people were in the low category with a percentage of 14%. It can be concluded that the level of procrastination in da'wah and communication faculty students is in the moderate category. With the results of the t-test analysis yielding tcount = 3.795 > ttable = 2.178 then Ha is accepted and Ho is rejected. Which means there is an influence on group counseling with reinforcement techniques to reduce procrastination behavior in students of the faculty of da'wah and communication.